DRINKING WATER QUALITY IN UZBEKISTAN: ENVIRONMENTAL CHALLENGES, REGIONAL DIFFERENCES, AND PUBLIC HEALTH RISKS (WITH A FOCUS ON KARAKALPAKSTAN) - Baimuratova D. K.; Niyazova O. A. (Bright Mind Publishing, 2025)
The article analyzes the current state of drinking water quality in Uzbekistan, identifies key environmental challenges, regional differences and potential risks to public health. Special attention is paid to Karakalpakstan, the region most vulnerable to water problems due to the drying up of the Aral Sea, land degradation and reduced availability of safe drinking water. Based on data from the World Health Organization, the State Committee for Ecology of Uzbekistan and scientific research, the main water pollutants, their origin and impact on public health are considered. Recommendations are made to improve the quality of drinking water and reduce environmental risks.
Keywords: Drinking water, Uzbekistan, Karakalpakstan, environmental risks, water quality, the Aral Sea, public health, pollution, sanitary standards.